The most common linkers in bioactive molecules and their bioisosteric replacement network. (1st March 2023) - Ertl, Peter; Altmann, Eva; Racine, Sophie
Graphical abstract: Abstract: Structures of the large majority of bioactive molecules are composed of several rings that are decorated by substituents and connected by linkers. While numerous cheminformatics studies focusing on rings and substituents are available, practically nothing has been published about the third important structural constituent of bioactive molecules - the linkers. The current study attempts to fill this gap. The most common linkers present in bioactive molecules are identified, their properties analyzed and a method for linker similarity search introduced. The bioisosteric replacement network of linkers is generated based on a large corpus of structure–activity data from medicinal chemistry literature. The results are presented in a graphical form and the underlying data are also made available for download. This analysis is intended to help medicinal chemists to better understand the role of linkers, particularly heterocyclic rings in bioactive molecules and to select an optimal set of linkers in their future project.